Offset-Free Robust Backstepping Position Control in a Nonlinear Electromagnetic Suspension System - Okumus, Eyup; Adiguzel, Fatih (IEEE, 2025)
In this paper, a precise position controller for a nonlinear voltage-controlled electromagnetic suspension system is presented through robust backstepping controller design with integral action. The designed controller focuses on canceling the effect of the bias and matched constant disturbances in the uncertain third-order suspension system. In the integral backstepping control design, the integral actions are defined based on the errors corresponding to the coil current and velocity of the magnetic ball; thus, by matching the integral term with the bias, offsets resulting from bias and parametric uncertainties are asymptotically suppressed. Accordingly, the asymptotic stability of the closed-loop system is shown in the sense of Matrosov's Theorem. To test the designed controller, simulation studies are conducted with comparative cases on the uncertain dynamics of the electromagnetic suspension system, including bias effects. The simulation results demonstrate that the devised controller for the voltage-controlled suspension system achieves the offset-free position against parametric uncertainties and constant voltage and current bias effects.
Keywords: offset-free position; backstepping; integral action; robust control; electromagnetic suspension system; LEVITATION; DESIGN; Energy & Fuels; Engineering